Analysis of prognosis and treatment decisions for patients with second primary lung cancer following esophageal cancer - Li, Jin-luan; Li, Hui; Wu, Qian; Zhou, Han; Li, Yi; Li, Yong-heng; Li, Jiancheng (Frontiers in Oncology, 2022)
Introduction As the long-term prognosis of esophageal cancer (EC) is improving, concerns of a second primary malignancy (SPM) have increased. However, research on lung cancer as the SPM after EC is limited. Therefore, we aimed to explore the prognostic factors and clinical treatment decisions of patients with second primary lung cancer following esophageal cancer (SPLC-EC). Materials and methods We identified the data of 715 patients with SPLC-EC from the Surveillance, Epidemiology, and End Results (SEER) database during 1975 to 2016. We established a nomogram through Cox regression modelling to predict the prognosis of patients with SPLC-EC. We determined the association between factors and cancer-specific mortality using the Fine-Gray competing risk model. Then, we performed survival analysis to evaluate the benefits of different treatment methods for overall survival (OS). Results The multivariate analysis indicated that sex, insurance recode, age, surgery and chemotherapy 0for first primary malignancy (FPM), primary site, stage, and surgery for SPM were independent prognostic factors for OS. Using concordance indices for OS, the nomogram of our cohort showed a higher value than the SEER historic-stage nomogram (0.8805 versus 0.7370). The Fine-Gray competing risk model indicated that surgery for FPM and SPM was the independent prognostic factor for EC-specific mortality (P=0.016, hazard ratio [HR] = 0.532) and LC-specific mortality (p=0.016, HR=0.457), respectively (p<0.001). Compared to the patient group having distant metastasis, patients with localized and regional metastasis benefitted from undergoing surgery for SPM (P<0.001, P<0.001, respectively). For patients without surgery for SPM, radiotherapy (P<0.001) and chemotherapy (P<0.001) could improve OS. Conclusions Surgery remains the mainstay for managing SPLC-EC, especially for localized and regional tumors. However, chemotherapy and radiotherapy are recommended for patients who cannot undergo surgery. These findings can have implications in the treatment decision-making for patients with SPLC-EC.